The Multiplicity of Performance Management Systems: Heterogeneity in Multinational Corporations and Management Sense‐Making - Cooper, David J.; Ezzamel, Mahmoud; Robson, Keith (Contemporary Accounting Research, 2019)
ABSTRACT This field study examines the workings of multiple performance measurement systems (PMSs) used within and between a division and Headquarters (HQ) of a large European corporation. We explore how multiple PMSs arose within the multinational corporation. We first provide a first‐order analysis which explains how managers make sense of the multiplicity and show how an organization's PMSs may be subject to competing processes for control that result in varied systems, all seemingly functioning, but with different rationales and effects. We then provide a second‐order analysis based on a sense‐making perspective that highlights the importance of retrospective understandings of the organization's history and the importance of various legitimacy expectations to different parts of the multinational. Finally, we emphasize the role of social skill in sense‐making that enables the persistence of multiple systems and the absence of overt tensions and conflict within organizations.